Measuring the Impact of Mechatronic Systems on Silkworm Egg Incubation for Premium Silk Yield - Bakhodirjon, Nasirdinov (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This study investigates the influence of mechatronic systems on silkworm seed incubation to enhance silk quality and yield. Through a controlled experimental approach, we analyzed the effects of a mechatronic environment on silkworm incubation. Our findings indicate significant improvements in silk quality and yield, providing a promising avenue for sustainable silk production. Silk has been prized for centuries due to its luxurious feel and exceptional qualities. The quality of silk heavily depends on the health and development of the silkworms. In this study, we explore the potential of mechatronic systems to optimize the incubation conditions of silkworm seeds, aiming for higher-quality silk.